Taming the Kosi River - J. S. Bali (Journal of Soil and Water Conservation, 2022)
Kosi, the river of sorrow of Bihar, is in the news. The news is really bad. As long expected by the professionals, embankment has breached. Fifty thousand persons in Nepal and 2.5 million in Bihar are experiencing the fury of the Kosi flood. It was heart-rending to see the helpless men, women and children, swept away in the Kosi current. The flood peak was less than 2 lakh causecs while 8 lakh causecs is the design peak flood. It is difficult to imagine what would have happened if the expected highest flood would have come. Some survivors were seen propitiating the angry river goddess by offering flowers and food. The belief is that every natural calamity is caused by a god or goddess who is angry because people have done something wrong. The Raja was never blamed. ‘Times of the Rajas have gone. Governments must be lamed for the Kosi Catastrophe